2019
DOI: 10.24874/ti.2019.41.02.04
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Tool Wear and Surface Characteristics in Hard Turning Under Air-Water Jet Spray Impingement Cooling Environment

Abstract: Low cost machining puts tremendous pressure on the research in machining hardened steel compared to traditional grinding. As environmental regulations are strict enough on application of cutting fluids, a novel method called spray impingement cooling (SIC) assisted hard turning has been studied. The current work explores the distinguish wear modes, surface characteristics, chip-tool interface temperature and chip morphology in turning of AISI D2 steel by coated carbide tools (TiN/TiCN/Al 2 O 3 /TiN). The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 26 publications
(48 reference statements)
1
3
0
Order By: Relevance
“…Blue colour chips denoted the higher heat generation compared to other machining tests where metallic chips produced. Similar illustration reported by [43].…”
Section: Chippingsupporting
confidence: 81%
See 1 more Smart Citation
“…Blue colour chips denoted the higher heat generation compared to other machining tests where metallic chips produced. Similar illustration reported by [43].…”
Section: Chippingsupporting
confidence: 81%
“…Tool-tip-lost Micro-chipping VBc impact analysis through ANOVA (Table 3), as the impact of feed (43.11 %) on CRC is about 2.54 times more than cutting speed (15.92%). Singh et al [43], also found a decrement in CRC with leading feed. ANOVA also reported that all the input terms significantly influence the CRC.…”
Section: Chippingmentioning
confidence: 87%
“…This equation is essential for machining parameters optimization. For this reason, starting with Taylor, this subject permanently came to the attention of researchers from the field [1,[37][38][39][40][41][42][43][44][45]. One of the commonly used tool life equations is the extended Taylor's tool life equation, as follows:…”
Section: Literature Reviewmentioning
confidence: 99%
“…Soybean oil-based Al2O3 nanofluid was recommended for the best quality finish. Dong et al [24] found the superior quality of surface finish with 0.5 weight % of MoS2 nanofluid MQL in hard machining of tool steel. Das et al [25] utilised rice bran oil-based three different nanofluid samples like Al2O3, Cuo and Fe2O3 in MQL hard turning and performance of CuO nanofluid was best among others nanofluids succeeded by Fe2O3 and Al2O3 nanofluids.…”
Section: Introductionmentioning
confidence: 99%